1993
DOI: 10.1172/jci116877
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous levels of the insulin-like growth factors I and II, and the insulin-like growth factor binding proteins 2 and 3, increase in neovascular eye disease. Studies in nondiabetic and diabetic subjects.

Abstract: Retinal capillary nonperfusion results in neovascularization of the eye, which is restricted to the retina in less severe cases and progresses to the anterior chamber and the iris angle in the most advanced case, called rubeosis. This angioneogenesis may be induced by the release of retinal growth factors into the vitreous. This study compared levels of the IGF-I and IGF-II, and of the IGF binding protein-2 (IGFBP-2) and IGFBP-3 in vitreous from three groups with different degrees ofretinal ischemia, as judged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
135
1
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(144 citation statements)
references
References 22 publications
6
135
1
2
Order By: Relevance
“…43 Vitreous IGF-I levels are increased in diabetic retinopathy. 26 In agreement, we now demonstrate that inhibition of IGF-I signaling down-regulates Akt activity and ICAM-1 expression, as well as the transcriptional activity of NF-B, AP-1, and HIF-1␣ in our in vivo diabetic model.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…43 Vitreous IGF-I levels are increased in diabetic retinopathy. 26 In agreement, we now demonstrate that inhibition of IGF-I signaling down-regulates Akt activity and ICAM-1 expression, as well as the transcriptional activity of NF-B, AP-1, and HIF-1␣ in our in vivo diabetic model.…”
Section: Discussionsupporting
confidence: 88%
“…21,[23][24][25] Yet, aside from hypoxia, additional factors may also regulate VEGF expression in vivo. Insulin-like growth factor (IGF)-I is one such candidate: vitreous IGF-I levels correlate with the presence and severity of ischemia-associated diabetic retinal neovascularization; 26 intravitreal IGF-I injection dose-dependently causes retinal neovascularization and microangiopathy; 27 whereas reduction of serum IGF-I levels inhibits retinal neovascularization in an ischemic murine model. 28 Pituitary ablation acutely improved visual acuity and suppressed proliferative diabetic retinopathy in some diabetic retinopathy patients, raising the hypothesis that decreases in growth hormone and IGF-I underlie this phenomenon.…”
mentioning
confidence: 99%
“…Recent studies suggest that interactions between IGF-I and its receptors enhance the angiogenic effects of VEGF [45]. These findings are consistent with the documented association between IGF-I and diabetic retinopathy [46] and suggest that both IGF-I and VEGF may contribute to the pathogenesis of vision-threatening retinal disease in diabetes. Thus, although a reduction in VEGF expression with ACE inhibitor treatment was noted in our study it is also possible that other intra-ocular growth factors such as IGF-I were also affected by modulation of the RAS as in the kidney [47].…”
Section: Discussionsupporting
confidence: 77%
“…With regard to the IGF system, in vivo studies show conflicting results: IGF-I concentrations in the vitreous of diabetic patients correlated positively with its serum concentrations (Grant et al 1986), whereas a weak increase in serum IGF-I was observed in patients with proliferative diabetic retinopathy (Bach & Rechler 1992), suggesting that locally high concentrations of IGF-I may be more important than systemic concentrations. In addition, IGFBPs were increased in the vitreous of neovascularised diabetic eyes (Meyer Schwickerath et al 1993). In vitro studies, indeed, have shown the IGF system to have a role in retinal endothelial cell proliferation.…”
Section: Introductionmentioning
confidence: 95%